ANALISIS PENGARUH PENERIMAAN PAJAK REKLAME DAN JUMLAH INDUSTRI TERHADAP PENDAPATAN ASLI DAERAH KOTA KUPANG - Septianus Boimata; Kretisana Jagi; Marselinda Hege; Joritha Naisanu; Yonatan Pering (Politeknik Negeri Ambon, 2023)
This study aims to determine the effect of advertisement tax and the number of industries on local revenue in Kupang City. This research was conducted at the Regional Revenue Office of Kupang City, East Nusa Tenggara. This research uses qualitative data. Sources of data in this study: Primary data and secondary data, namely data obtained through documents contained in the Regional Revenue Service of Kupang City and BPS-NTT. Data collection techniques are carried out by: Interviews and Documentation. Data analysis technique using multiple regression analysis. The results obtained: billboard tax affects local revenue at a confidence level of 99%, the number of industries affects local revenue at a confidence level of 95%, and simultaneously advertisement tax and the number of industries affect local revenue.